Analysis Of Judge's Decision Against Substitute Charities In Religious Courts Consider From Islamic Law Commission - Rikson Adam; Erman Rahim; Abdul Hamid Tome (Estudiante Law Journal, 2022)
The purpose of this study is to analyze the judge's decision in case number: 132/Pdt.P/2019/PA.Gtloviewed from the Compilation of Islamic Law This research uses a normative-empirical legal research type, where an analysis of the written law is carried out with factual events in the field. In this study, the data sources used are primary data consisting of the results of interviews and field observations, the Civil Code, ILC, and judges' decisions related to the issues being discussed; and secondary data (supporting) scientific works, and other sources related to the problems discussed.The results of the study show that first, the substitute heirs proposed by the applicants in case no. 132/Pdt.P/2019/PA.Gtlo from the late. Zubaida Datau may become a substitute heir based on the provisions formulated in the Compilation of Islamic Law (ILC), provided that the plot of land is the property of the late. Saini Datau. However, if the plot of land is the property of the Almh. Kamaria Datau, then the substitute heir proposed by the applicant, must be declared not accepted by the panel of judges at the Gorontalo PA because he is prevented from becoming an heir based on the ILC formulation. Legal considerations of the panel of judges examining case No. 132/Pdt.P/2019/PA.Gtlo, where the case is declared unacceptable, is that it is unclear/fuzzy, no longer voluntary, but a contentious case, because it contains a dispute between the heirs of the deceased's heirs. Kamaria Datau, and the late. Zubaida Datau.